Conifer fossil woods from the La Meseta Formation (Eocene of Western Antarctica): Evidence of Podocarpaceae-dominated forests - Pujana, Roberto Roman; Santillana, Sergio; Marenssi, Sergio Alfredo (Review of Palaeobotany and Palynology)
A new collection of 120 fossil wood samples from early Eocene sediments of the La Meseta Formation is studied. Conifers represent 68 % of the total amount of wood samples. The specimens show significant conifer diversity and were placed in seven fossil-species. Samples are assigned to the Podocarpaceae, probably Cupressaceae and Araucariaceae. New fossil-species of Protophyllocladoxylon and Phyllocladoxylon (Podocarpaceae) and two new nomenclatural combinations are proposed. Comments about the systematic position of each genus and species represented are made. The systematic is based on anatomical data and supported by statistical analysis. A PCA of 78 woods and 12 characters was performed to confirm the taxon delimitation and discrete clusters are represented in the plots for most of each species. Phyllocladoxylon antarcticum is the most common wood type followed by Cupressinoxylon, Agathoxylon and other Podocarpaceae. In accordance with previous studies, our samples suggest that during the early Eocene forests of the northeastern part of the Antarctic Peninsula were dominated by conifers, particularly Podocarpaceae. Fil: Pujana, Roberto Roman. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Parque Centenario. Museo Argentino de Ciencias Naturales "Bernardino Rivadavia"; Argentina Fil: Santillana, Sergio. Ministerio de Relaciones Exteriores, Comercio Interno y Culto. Dirección Nacional del Antártico. Instituto Antártico Argentino; Argentina Fil: Marenssi, Sergio Alfredo. Ministerio de Relaciones Exteriores, Comercio Interno y Culto. Dirección Nacional del Antártico. Instituto Antártico Argentino; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina. Universidad de Buenos Aires; Argentina